2017
DOI: 10.1039/c7ra11892a
|View full text |Cite
|
Sign up to set email alerts
|

One pot synthesis of NiMo–Al2O3 catalysts by solvent-free solid-state method for hydrodesulfurization

Abstract: A simple and solvent-free solid-state method was used to prepare NiMo–Al2O3 hydrodesulfurization (HDS) catalysts using Ni(NO3)2·6H2O, (NH4)6Mo7O24·4H2O, and AlCl3·6H2O as the solid raw materials and polyethylene glycol (PEG) as an additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Owing to the low concentration, well dispersion, and small size of cobalt and nickel particles, the weakly associated peaks were obtained. Such behavior was also reported in the previous studies dedicated to NiMo [78][79][80][81] and CoMo [82,83] catalysts. The wt.%, as well as well particle distribution, were obtained by EDXS and mapping analysis (Table 1 and Figures S1-S4).…”
Section: Catalyst Characterizationssupporting
confidence: 87%
“…Owing to the low concentration, well dispersion, and small size of cobalt and nickel particles, the weakly associated peaks were obtained. Such behavior was also reported in the previous studies dedicated to NiMo [78][79][80][81] and CoMo [82,83] catalysts. The wt.%, as well as well particle distribution, were obtained by EDXS and mapping analysis (Table 1 and Figures S1-S4).…”
Section: Catalyst Characterizationssupporting
confidence: 87%
“…As shown in Figure 4, the reducibility of nickel‐molybdenum bimetallic nitrides catalysts is evaluated. The peak between 200–450 °C could be assigned to the reduction of surface oxides [23] …”
Section: Resultsmentioning
confidence: 99%
“…The peak between 200-450 °C could be assigned to the reduction of surface oxides. [23] The Mo 2 N sample has a higher-temperature H 2 -consuming peak at 436.…”
Section: The Physicochemical Properties Of Nickel Molybdenum Bimetall...mentioning
confidence: 99%
“…Carbonaceous residua could also act as spacer hindering sulfided phases sintering thus improving their dispersion. In this line, Yi et al reported [68] preparation of NiMo-based catalaysts in presence of polyethylene glycol (PEG) by using their solvent-free solid-state method. Based in their results that group claimed that when in suitable amount PEG addition rendered materials of improved sulfidability and active MoS 2 dispersion the latter effect being caused by carbonaceous residua blocking Ni and Mo phases aggregation avoiding then formation of large clusters.…”
Section: Sulfided Catalysts Characterization Of By High-resolution Electron Microscopy (Hr-tem)mentioning
confidence: 99%